NetworkDCQ: A multi-platform networking framework for mobile applications - Cristina, Federico (2013)
Currently, the number of mobile applications that require (wireless) connectivity is constantly increasing. The need for sharing information among mobile devices exists in many applications, and almost every data exchange between these devices involve the same requirements: a means for discovering other mobile devices in a wireless network, establishing logical connections, communicating application data, and gathering information related to the physical connection. This paper proposes an open source developer-oriented framework that acts as a network support layer for host discovery, data communication among devices, and quality of service characterization, which can be used for developing several types of applications and is proposed for different platforms, such as Android Java, J2SE, and J2ME.